Reflecting on the Teaching Analysis of Pictorial Geometry and Mechanical Drawing Course from the Cultivation of Engineering Design Ability (Contemporary Education and Teaching Research, 2023)
Along with the deepening of education and teaching curriculum reform in the new era, it also fully promotes the new development of teaching curriculum of pictorial geometry and mechanical drawing course. Traditional teaching methods and teaching concepts are no longer applicable to students at this stage, and pictorial geometry is the most basic professional course in a mechanical drawing course, teachers should focus their teaching on the cultivation of students' engineering design ability, deepen the education and teaching reform of mechanical drawing course, fully carry out the creation of diversified teaching classes, and establish a perfect modular teaching system, so that students can more intuitively, comprehensively and effectively master mechanical drawing course. In this way, students can master the knowledge of mechanical drawing courses more intuitively, comprehensively and effectively, and further promote the comprehensive development of students' overall quality. This paper discusses "reflecting on the teaching analysis of pictorial geometry and mechanical drawing course from the cultivation of engineering design ability" for reference only.